2002
DOI: 10.1074/jbc.m202203200
|View full text |Cite
|
Sign up to set email alerts
|

Several PATCHED1 Missense Mutations Display Activity in patched1-Deficient Fibroblasts

Abstract: Mutations in mouse and human patched1 (ptc1) genes are associated with birth defects and cancer. Ptc1 is a receptor for Hedgehog (Hh) signaling proteins. Hh proteins activate transcription of target genes, including ptc1, and Ptc1 represses those genes, both by regulating the activity of Gli transcription factors. We have established mammalian cell lines with reduced Ptc1 function and a lacZ reporter to investigate Hh signal transduction. Embryonic fibroblasts were derived from mice, heterozygous or homozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 69 publications
1
26
1
Order By: Relevance
“…PTCH1 protein truncation mutations (observed in 86% of the NBCCS cases) often manifest as PTCH1 haploinsufficiency, as neither the N-nor the C-terminal half of PTCH1 is functional alone. (38,39) PTCH1 missense mutations have also been reported to result in variable levels of PTCH1 function, with some (Q802L and P1111L) associated with significant retention of activity, some (eg, L346R) causing only modest reduction in activity, and others resulting in substantial loss of function (R280C, G495V, and D499Y). (40,41) Consequently, the missense mutations in the remaining 4 cases (NB5, 9, 11, and 12) may have resulted in the partial retention of function, as a result of which these cases exhibited intermediate levels of PTCH1 activity compared with the wild-type and haploinsufficient lines.…”
Section: Discussionmentioning
confidence: 99%
“…PTCH1 protein truncation mutations (observed in 86% of the NBCCS cases) often manifest as PTCH1 haploinsufficiency, as neither the N-nor the C-terminal half of PTCH1 is functional alone. (38,39) PTCH1 missense mutations have also been reported to result in variable levels of PTCH1 function, with some (Q802L and P1111L) associated with significant retention of activity, some (eg, L346R) causing only modest reduction in activity, and others resulting in substantial loss of function (R280C, G495V, and D499Y). (40,41) Consequently, the missense mutations in the remaining 4 cases (NB5, 9, 11, and 12) may have resulted in the partial retention of function, as a result of which these cases exhibited intermediate levels of PTCH1 activity compared with the wild-type and haploinsufficient lines.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, two other studies have examined the molecular basis of several human ptc1 mutants identified from NBCCS/ BCC patients (Bailey et al, 2002(Bailey et al, , 2003. Results from these studies demonstrated that ptc1 mutants unable to mature have reduced protein stability and are unable to inhibit endogenous ptc1 promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…The probes for GLI1 and PATCHED1 have been previously described (Bailey et al, 2002). The b-actin exposures for the blots in Figure 1d have been previously published (Zwerner and May, 2001).…”
Section: Northern Blotsmentioning
confidence: 99%